Komunikasi Interpersonal Ibu Tunggal dan Anak Penyandang Disabilitas - Deni Yanuar; Zakirah Azman; Eni Tri Retnaningsih (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2019)
This study aims to find out the interpersonal communication between single mothers with their children with disabilities in Aceh. The research used symbolic interaction theory with a qualitative descriptive approach. The subject of this study was a single mother who has children with disabilities studying at SMALB YPPC Banda ACEH, selected using a purposive sampling technique. To collect data, the researchers deployed semi-structured interviews on three single mothers who have children with disabilities and observations of their interpersonal communication with their children. The results showed that interpersonal communication of single mothers and children with disabilities varies depending on the child's condition. Many mothers used non-verbal communication especially with deaf children and spoke slowly so that their children could easily understand. In the communication process, single mothers often faced obstacles to get feedback which sometimes caused misunderstandings. The quality of communication, in general, is good because the children demonstrated openness, empathy, support, and positive attitudes in communicating with their mothers.